Balance in resolution of collision of fundamental rights. Special reference to the Spanish constitutional jurisprudence - Ruiz-Ruiz, Ramón (Universidad Pedagógica y Tecnológica de Colombia, 2013)
For the study of the balance in the resolution of collision of fundamental rights, in particular concerning to the Spanish constitutional jurisprudence, is necessary to see the distinction between rules and principles: the strong thesis of separation; at the same time the role of the principles in legal reasoning and last, the law collision in Spanish constitutional jurisprudence.